Enhanced Antiviral Activity of Human Surfactant Protein D by Site-Specific Engineering of the Carbohydrate Recognition Domain - van Eijk, Martin; Hillaire, Marine L. B.; Rimmelzwaan, Guus F.; Rynkiewicz, Michael J.; White, Mitchell R.; Hartshorn, Kevan L.; Hessing, Martin; Koolmees, Peter A.; Tersteeg, Monique H.; van Es, Maarten H.; Meijerhof, Tjarko; Huckriede, Anke; et al. (Frontiers in Immunology, 2019)
Innate immunity is critical in the early containment of influenza A virus (IAV) infection and surfactant protein D (SP-D) plays a crucial role in innate defense against IAV in the lungs. Multivalent lectin-mediated interactions of SP-D with IAVs result in viral aggregation, reduced epithelial infection, and enhanced IAV clearance by phagocytic cells. Previous studies showed that porcine SP-D (pSP-D) exhibits distinct antiviral activity against IAV as compared to human SP-D (hSP-D), mainly due to key residues in the lectin domain of pSP-D that contribute to its profound neutralizing activity. These observations provided the basis for the design of a full-length recombinant mutant form of hSP-D, designated as ‘improved SP-D’ (iSP-D). Inspired by pSP-D, the lectin domain of iSP-D has 5 amino acids replaced (Asp324Asn, Asp330Asn, Val251Glu, Lys287Gln, Glu289Lys) and 3 amino acids inserted (326Gly-Ser-Ser). Characterization of iSP-D revealed no major differences in protein assembly and saccharide binding selectivity as compared to hSP-D. However, hemagglutination inhibition measurements showed that iSP-D expressed strongly enhanced activity compared to hSP-D against 31 different IAV strains tested, including (pandemic) IAVs that were resistant for neutralization by hSP-D. Furthermore, iSP-D showed increased viral aggregation and enhanced protection of MDCK cells against infection by IAV. Importantly, prophylactic or therapeutic application of iSP-D decreased weight loss and reduced viral lung titers in a murine model of IAV infection using a clinical isolate of H1N1pdm09 virus. These studies demonstrate the potential of iSP-D as a novel human-based antiviral inhalation drug that may provide immediate protection against or recovery from respiratory (pandemic) IAV infections in humans.